Education Under the Islamic State of Iraq and Syria: A Content Analysis of the Physical Education Curriculum - Gadais, Tegwen; Touir, Ghada; Décarpentrie, Laurie; Al-Khatib, Mazen; Daou, Alain; Chamsine, Chirine; Arvisais, Olivier (Frontiers in Education, 2022)
This study focused on what lessons can be learned from the Physical Education Curriculum under the reign of Islamic State of Iraq and Syria (ISIS)? We conducted an unprecedented analysis of ISIS primary school physical education curriculum. The research objective focused on describing and analyzing the context and intentions of the document as well as its content (didactic, pedagogy, learning assessment, among others). We also analyzed the general scientific quality of the curriculum of physical education targeting fitness preparation by the instructor in charge of the education of the youth. In addition, our analysis focused on the philosophical and contextual issues of the manual. Findings revealed an incomplete and a rapidly developed textbook where several essential elements related to pedagogy, didactics, learning and assessment were missing or inconsistent. The logic of military preparation under the guise of preparing the student’s physical condition was an important finding without being explicitly mentioned. Integration of religious content was present without being affirmed in the content of the lessons. We argue that the ISIS physical education curriculum appears to be committed to an absolutist/theocratic ideological or propaganda program that, among other things, promotes the preparation of the future soldiers of the ISIS army. Recommendations about secularization and the reconstruction of post-ISIS education systems are formulated.